Evaluation of an automated temperature control equipment for lactating sows - Fernandes, Renato Mattos; Maciel, Maria Luiza dos Santos; Souza, Alexandre Vinhas de; Amaral, Leticia Gomes de Morais; Amaral, Nikolas de Oliveira (Acta Scientiarum. Animal Sciences, 2022)
The present study aimed to develop and evaluate an automated cooling control system (ATCE) for sows in the farrowing phase. The experiment was conducted at the Swine Production Unit, Federal Institute of Education, Science and Technology, Campus Machado, Machado, state of Minas Gerais. Sixteen sows and their offspring were evaluated, eight treated and eight controls, in a randomized block design, with eight replications. Surface temperature, body temperature and respiratory rate of the animals were evaluated, in addition to floor temperature and performance parameters. The use of ATCE decreased the floor temperature (12h) and neck temperature (12 and 16h) (p < 0.10). In addition, there was a reduction in rectal temperature (12h) and respiratory rate (12 and 16h) in ATCE animals (p < 0.10). No significant differences were detected in the coefficient of variation (CV) of birth weight, but at weaning the CV of piglet weight was 26.3% lower in animals subjected to the ATCE (p = 0.079). Furthermore, the difference in CV between birth and weaning was also lower with the use of ATCE (p = 0.015). It can be concluded that the use of ATCE has a positive influence on the thermal comfort of females, in addition to improving litter uniformity.